Public Utility Rate Making in Depression: A Comment - Sumner, John D. (Quarterly Journal of Economics, 1938)
Journal Article Public Utility Rate Making in Depression: A Comment Get access John D. Sumner John D. Sumner The University of Buffalo Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 52, Issue 4, August 1938, Pages 713–717, https://doi.org/10.2307/1885043 Published: 01 August 1938